The Fate of Central Asian Spiritual Heritage (Late 19th - Early 20th Centuries) - Latofat Samievna Kholnazarova; Khairullaeva Dildora Saidullayevna (International Journal on Integrated Education, 2022)
This article focuses on the confiscation of valuable rare manuscripts written by the peoples of Central Asia in the late 19th and early 20th centuries by orient lists from the Russian Empire and other foreign countries, as well as foreign travelers and researchers. Orientals A.L. Kun, a consultant who took part in the conquest of the khanates, was involved in the seizure of valuable manuscripts and their sale and donation in various libraries around the world. There is also important information that Amir Muzaffar and Sayyid Alimkhan presented rare manuscripts to Russian emperors.